Exploring educational leaders' motivation strategies in enhancing teachers' performance : a case study of Baseerah International School Malaysia - Abouelnasr, Doaa Fawzi Mohamed Saadeldin (Kulliyyah of Education, International Islamic University Malaysia, 2017)
The purpose of this research is to explore the educational leaders' motivation strategies in enhancing teachers' performance in the context of a case study in Baseerah International School (BIS), Kuala Lumpur, Malaysia. The main purpose of the study is to explore the motivation strategies that are implemented by the educational leaders in BIS and how these strategies influence teachers' performance in terms of satisfaction and dissatisfaction from teachers' perspective. A qualitative research design was employed to collect data from the selected teachers in BIS. The individuals were interviewed as the process of the data collection. The sample population consists of five teachers with teaching experience of not less than one year. Participants responded to open-ended interviews questions in order to investigate how educational leaders' strategies and practices have influenced the teachers' performance and motivation. As perceived by the teachers, the findings have found that there are certain educational leaders' practices that impact teachers' performance and motivation negatively. These cause dissatisfaction such as lack of intrinsic and extrinsic motivation, lack of contribution in decision making, lack of teachers' autonomy, and work overload among the teachers in BIS. The implications to enhance teachers' performance include improving educational leaders' strategies and practices through specialized training programs to help in motivating teachers and enhance their performance.